KETERATURAN PENIMBANGAN DENGAN PERTUMBUHAN ANAK BALITA DI DESA GAYAMAN KECAMATAN MOJOANYAR KABUPATEN MOJOKERTO - SUSANTI, IKA YUNI; wardini Pujilestari, Sri; Rufaida, Zulfa (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2018)
Weighing the activities carried out in posyandu each once a month which aims to monitor the growth of infants and early detection of growth disorders. To achieve a small family, happy and sejahteraa undertaken by the family with the community with guidance from local health officials. This study aims to determine the relationship with the growth of infants weighing regularity in the Village District Gayaman, Mojoanyar, Mojokerto. The design used was an observational analytic type "Cross Sectional", with a sample of 63 mothers and young children who come to posyandu where the researchers used a technique of sampling proportions (proportional sample). Data was then incorporated in the cross tabulations are calculated using a statistical test of"Chi-Square". Based on the results obtained from 63 respondents over half of respondents do not regularly weighing as many as 40 respondents (63.47%) and less than half the growth of children under five underweight were 24 respondents (38.09%). So that the calculation of the relationship with the growth of infants  =aweighing regularity performed with chi-square test with df = 3 and  0.05 obtained by calculating the X2 X2 = 14.05, while table = 7.815 The mean count X2> X2 table that is Ho refused and Ha accepted that there is a relationship with the growth of infants weighing regularity.Weighing regularity associated with the growth due to the regular weighing of the growth will be increasingly monitored, and if there is a disturbance of growth will soon be given the appropriate intervention. And vice versa if the weighing is done the irregular growth of the disturbance would not be detected early.The results of this study can be concluded that the order can affect the growth of infants weighing. So the mother came to posyandu regularly then the observed growth of these infants. Thus the effort to improve the regularity of such judgments necessary to improve the provision of counseling because of the high knowledge will foster a heightened awareness as well. Keywords: Regularity, Weighing, Infants